Cesarean Wound Risk Assessment and Management: A Quality Improvement Study [35I]. (May 2018) - Griffiths, Kara M.; Nguyen, Xuan-Loc; Maxwell, Rose; Polenakovik, Hari; Shahin, Maryam; Galloway, Michael
Abstract : INTRODUCTION: Surgical site infections (SSIs) represent approximately 17% of all hospital-acquired infections with an estimated 500, 000 SSIs per year. Cesarean delivery is the primary contributor to SSIs, resulting in patient morbidity and increasing length of hospital stay and medical costs. Studies have shown a benefit to pre-operative antibiotics, but no studies have been done to determine the benefits of stratifying patients into risks categories to tailor management with the goal of preventing infection. METHODS: This is a prospective two-phase quality improvement study in which women undergoing cesarean delivery were categorized according to a risk stratification checklist into high and low-risk groups for developing SSIs. Management for the low risk group consisted of standard pre-operative intravenous antibiotics and a standard pressure dressing. Management for the high risk group consisted of 24 hours of intravenous antibiotics and a specialized Mepilex dressing. SPSS software was used for data analysis. RESULTS: The overall occurrence of SSIs in the low and high risk groups were 7.1% and 3.3% respectively, p-value <0.23. 20% of patients with SSIs had insulin-controlled diabetes, p-value <0.06. Logistic regression demonstrated that both diabetes and BMI were strong predictors of SSIs, p-value <0.01. The incidence of complex SSIs decreased 40% after initiation of the protocol. CONCLUSION: Our data suggest an overall decrease in SSIs after stratifying patients into high and low risk groups with the assigned antibiotics/dressing. Obesity and diabetes are the greatest predictors of SSIs. These risk factors should prompt consideration of use of prolonged antibiotics and a specialized dressing.